Addressing disparities in pharmacogenomics through rural and underserved workforce education - Brown, Jacob T.; McGonagle, Erin; Seifert, Randall; Speedie, Marilyn; Jacobson, Pamala A. (Frontiers in Genetics, 2023)
Abstract Introduction: While pharmacogenomic (PGx) testing is routine in urban healthcare institutions or academic health centers with access to existing expertise, uptake in medically-underserved areas is lagging. The primary objective of this workforce education program is to extend access to didactic, case-based and clinical PGx training for pharmacists serving rural Minnesota and populations experiencing health disparities in Minnesota. Methods: A PGx workforce training program funded through the Minnesota Department of Health was offered through the University of Minnesota College of Pharmacy (COP) to pharmacists working in rural and/or underserved areas in the state of Minnesota. Learning activities included a 16-week, asynchronous PGx didactic course covering PGx topics, a 15-minute recorded presentation, an in-person PGx case-based workshop, and a live international PGx Conference hosted by the University of Minnesota COP and attendance at our PGx Extension of Community Health Outcomes (ECHO). Results: Twenty-nine pharmacists applied for the initial year of the program, with 12 (41%) being accepted. Four (33%) practiced in a hospital setting, four (33%) in retail pharmacy, two (17%) in managed care, and two (17%) in other areas. The majority had not implemented a PGx program as part of their practice, although nearly all responded definitely or probably yes when asked if they expected their organization to increase its use of PGx testing services over the next three years. All participants either strongly or somewhat agreed that this program helped them identify how and where to access clinical PGx guidelines and literature and improved their ability to read and interpret PGx test results. Eight participants (67%) strongly or somewhat agreed that they expected to increase the number of PGx consultations in their practice, while ten (83%) strongly or somewhat agreed they would be able to apply what they learned in this program to their practice in the next six months to a year. Discussion: This novel PGx training program focused on pharmacists in rural and/or underserved areas with a delivery method that could be accomplished conveniently and remotely. Although most participants’ organizations had yet to implement PGx testing routinely, most anticipated this to change in the next few years.